Cystic fibrosis in a Hispanic adolescent. Issue 3 (8th February 2013) - Lin, Jenny H.; Collaco, Joseph M.; Paranjape, Shruti M.
Abstract We describe the presentation of a Hispanic adolescent with chronic respiratory symptoms and poor growth that led to a diagnosis of cystic fibrosis (CF) based on an indeterminate sweat chloride result and DNA sequence analysis that revealed a single new frameshift mutation, Nt3878insATCAG, which results in a premature stop codon in exon 20 of the CFTR gene. This case, highlighted by the identification of a deleterious, disease‐causing mutation, illustrates the importance of maintaining both a high clinical suspicion for CF and low threshold for obtaining genetic testing in a non‐Caucasian Hispanic adolescent with a characteristic clinical presentation. Pediatr Pulmonol. 2014; 49:E40–E41. © 2013 Wiley Periodicals, Inc.